Utilization and Satisfaction of Basic Guidance Services of High School Students in a Catholic School - Vergara, MSLT, Ma. Dionita V.; Magallanes , Celo I. (Philippine Social Science Journal, 2020)
One of the primary functions of education is to provide students with opportunities to maximize their full potentials in all areas of life. A school’s guidance and counseling program’s function is to offer a broad spectrum of services to facilitate students’ growth and development. These services include but are not limited to individual inventory, information service, counseling, service, placement service, and follow up service. Hence, this paper describes the extent of utilization and the degree of satisfaction of high school students in a Catholic school in Antique during the school year 2019-2020. Likewise, it explores the significant difference in the extent of utilization and the degree of satisfaction vis-à-vis the respondent’s sex and grade levels.